PENANGANAN PRAKTIK JUDI (TOGEL) OLEH POLRES AIMAS DI KABUPATEN SORONG - Rofiq, Muhammad; Labolo, Aly Mustaqim (Muadalah : Jurnal Hukum, 2023)
In this research the author uses an empirical legal approach, namely research that is used to solve research problems by conducting primary data research in the field, in this case related to the role of the police in efforts to deal with lottery gambling in Aimas, Sorong Regency, as well as the inhibiting factors faced in overcoming it. lottery gambling. The data presented is from data sources which include primary data and secondary data, namely data obtained in the form of facts or information from research results directly at the research location. Meanwhile, secondary legal materials consist of all legal publications which are not official documents which provide explanations of primary legal materials in the form of literature and journals related to the role of the police in tackling lottery gambling in Aimas, Sorong Regency.